Tree Species Identification on Large Scale Aerial Photographs at New Forest - Tiwari, K. P. (Indian Forester, 1975)
Tree species identification on large scale (1:5,000) black and white aerial photographs at New Forest have been attempted. A dichotomous photo-interpretation key for twenty two species occurring in the area have been prepared and a comparison with the identification on medium scale (1:20,000) have been made. The necessity and usefulness of such detailed studies on tree species identification along with the evaluation of reflectance properties of tree species at age and different time of the year have been suggested for forest inventory purposes.